Simian malaria in wild macaques: first report from Hulu Selangor district, Selangor, Malaysia. (December 2015) - Akter, Rumana; Vythilingam, Indra; Khaw, Loke; Qvist, Rajes; Lim, Yvonne; Sitam, Frankie; Venugopalan, Balan; Sekaran, Shamala
Abstract Background Malaria is a vector-borne parasitic disease which is prevalent in many developing countries. Recently, it has been found thatPlasmodium knowlesi, a simian malaria parasite can be life-threatening to humans. Long-tailed macaques, which are widely distributed in Malaysia, are the natural hosts for simian malaria, includingP. knowlesi. The aim of the present study was to determine the prevalence of simian malaria parasites in long-tailed macaques in the district of Hulu Selangor, Selangor, Malaysia. Methods A total of 70 blood samples were collected fromMacaca fascicularis dwelling in the forest of Hulu Selangor by the Department of Wildlife and National Parks Peninsular Malaysia, Kuala Lumpur, Malaysia. DNA was extracted using PureLink™ Genomic DNA Kits. Conventional and nested PCR were used to detect the genus and species ofPlasmodium parasites respectively. In addition, phylogenetic analysis was carried out to confirm the species ofPlasmodium parasites. Results Thirty-five (50 %) of the 70 samples were positive forPlasmodium using genus-specific primers. These positive samples were then subjected to nested PCR targeting the 18S ribosomal RNA genes to detect all five simian malaria parasites: namely, P. knowlesi, Plasmodium inui, Plasmodium cynomolgi, Plasmodium fieldi, andPlasmodium coatneyi. All five species of simian malaria parasites were detected. Of these, P. inui was the predominant (65.7 %), followed byP. knowlesi (60 %), P. cynomolgi (51.4 %)P. coatneyi (45.7 %) andP. fieldi (2.9 %). A total of nine macaques had mono-infection withP. knowlesi (four), P. cynomolgi (two), P. coatneyi (two) andP. fieldi (one). Eleven of the macaques had dual infections while 12 had triple infections. Three macaques were infected with four species ofPlasmodium . Molecular and phylogenetic analysis confirmed the five species ofPlasmodium parasites. Conclusion This study has provided evidence to elucidate the presence of transmission of malaria parasites among the local macaques in Hulu Selangor. Since malaria is a zoonosis, it is important to determine the new control strategies for the control of malaria.